Pengembangan Peta Interaktif Tiga dimensi (3D) Gedung STMIK AMIK Riau Menggunakan Unity Engine - T.Sy Eiva Fatdha; Falendra (STMIK KHARISMA Makassar, 2016)
Along with the development of technology such as this, the use of the concept of three-dimensional (3D) graphics in the world began much-loved by many. The use of a 3D map has also been widely applied in the construction of which has the advantage that their map is much clearer than the two-dimensional (2D). When this has been a lot of software that offers 3D features, one example adalah.Unity Engine is a game engine with the popularity continues to grow pursue some specific game engine, such as the Unity Engine, Source Engine, or the Cry Engine. Unity is a game engine with a proprietary source license, but for a development license is divided into two, namely free and paid appropriate target device application development.